Aberrant hippocampus and amygdala morphology associated with cognitive deficits in schizophrenia - Peterson, Bradley S.; Kaur, Tejal; Sawardekar, Siddhant; Colibazzi, Tiziano; Hao, Xuejun; Wexler, Bruce E.; Bansal, Ravi (Frontiers in Cellular Neuroscience, 2023)
Background: Working memory deficits are thought to be a primary disturbance in schizophrenia. We aimed to identify differences in morphology of the hippocampus and amygdala in patients with schizophrenia compared with healthy controls (HC), and in patients who were either neuropsychologically near normal (NPNN) or neuropsychologically impaired (NPI). Morphological disturbances in the same subfields of the hippocampus and amygdala, but of greater magnitude in those with NPI, would strengthen evidence for the centrality of these limbic regions and working memory deficits in the pathogenesis of schizophrenia. Methods: We acquired anatomical MRIs in 69 patients with schizophrenia (18 NPNN, 46 NPI) and 63 age-matched HC participants. We compared groups in hippocampus and amygdala surface morphologies and correlated morphological measures with clinical symptoms and working memory scores. Results: Schizophrenia was associated with inward deformations of the head and tail of the hippocampus, protrusion of the hippocampal body, and widespread inward deformations of the amygdala. In the same regions where we detected the effects of schizophrenia, morphological measures correlated positively with the severity of symptoms and inversely with working memory performance. Patients with NPI displayed a similar pattern of anatomical abnormality compared to patients with NPNN. Conclusions: Our findings indicate that anatomical abnormalities of the hippocampus relate to working memory performance and clinical symptoms in persons with schizophrenia. Moreover, NPNN and NPI patients may lie on a continuum of severity, both in terms of working memory abilities and altered brain structure, with NPI patients being more severe than NPNN patients in both domains.